A review of detrusor overactivity and the overactive bladder after radical prostate cancer treatment. (3rd July 2015) - Thiruchelvam, Nikesh; Cruz, Francesco; Kirby, Mike; Tubaro, Andrea; Chapple, Christopher R.; Sievert, Karl‐Dietrich
Abstract : There are various forms of treatment for prostate cancer. In addition to oncologic outcomes, physicians, and increasingly patients, are focusing on functional and adverse outcomes. Symptoms of overactive bladder (OAB), including urinary frequency, urgency and incontinence, can occur regardless of treatment modality. This article examines the prevalence, pathophysiology and options for treating OAB after radical prostate cancer treatment. OAB seems to be more common and severe after radiation therapy than after surgical therapy and even persisted longer with complications, suggesting an advantage for surgery over radiotherapy. Because OAB that occurs after radical prostate surgery or radiotherapy can be difficult to treat, it is important that patients are made aware of the potential development of OAB during counselling before decisions regarding treatment choice are made. To ensure a successful outcome of both treatments, it is imperative that clinicians and non‐specialists enquire about and document pretreatment urinary symptoms and carefully evaluate post‐treatment symptoms.